2020
DOI: 10.1371/journal.pone.0242463
|View full text |Cite
|
Sign up to set email alerts
|

Developing and validating the Psychosocial Burden among people Seeking Abortion Scale (PB-SAS)

Abstract: While there is a large body of research demonstrating that having an abortion is not associated with adverse mental health outcomes, less research has examined which factors may contribute to elevated levels of mental health symptoms at the time of abortion seeking. This study aims to develop and validate a new tool to measure dimensions of psychosocial burden experienced by people seeking abortion in the United States. To develop scale items, we reviewed the literature including existing measures of stress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 50 publications
0
20
0
1
Order By: Relevance
“…Using the 4-item Perceived Stress Scale (PSS-4), Harris et al [ 10 ] revealed minimal stress among 254 women seeking first-trimester abortions in the U.S. (mean of 4.2 on a 0–16 scale). Another study also conducted in the U.S. reported an average PSS-4 score of 7.24 among 784 women at the time of abortion seeking but placed no limitation on gestational age [ 11 ]. Variability in findings may be related to heterogeneity in women's gestation and reliability of the PSS-4.…”
Section: Introductionmentioning
confidence: 99%
“…Using the 4-item Perceived Stress Scale (PSS-4), Harris et al [ 10 ] revealed minimal stress among 254 women seeking first-trimester abortions in the U.S. (mean of 4.2 on a 0–16 scale). Another study also conducted in the U.S. reported an average PSS-4 score of 7.24 among 784 women at the time of abortion seeking but placed no limitation on gestational age [ 11 ]. Variability in findings may be related to heterogeneity in women's gestation and reliability of the PSS-4.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature reveals that the percentage of abortion patients describing their pregnancy as wanted or meaningful ranges from as low as 11% to as high as 63% [ 6 ]. A more recent study has reported that only 42% of women receiving induced abortions identify the pregnancy as unwanted [ 14 ]. Therefore, without survey data regarding the intentionality of and/or emotional attachment to these pregnancies, our findings cannot distinguish between intentional replacement pregnancies, unconsciously desired replacement pregnancies, contraceptive failures, or lack of contraceptive use.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, despite data showing that depriving women of their reproductive rights has negative consequences on maternal and offspring mental health and that those limitations disproportionately impact minorities, women remain hostage to restrictive laws and scarcity of resources in several parts of the globe [63].…”
Section: Perimenopausementioning
confidence: 99%